2023
DOI: 10.5267/j.ijdns.2022.10.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of e-WOM model mediation of marketing mix and destination image on tourist revisit intention

Abstract: Word-of-mouth (WOM) has been recognized as one of the most influential forms of information transmission. Advances in information technology and the emergence of online social networking sites have changed the manner in which data is delivered. This phenomenon has an impact on consumers because readily accessible information can significantly influence consumption-related decisions. The purpose of this paper is to examine the role of e-WOM in mediating the influence of the marketing mix and destination image o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In addition to a wider reach, communication through E-WOM is more easily believed that can influence the formation of purchasing decisions (Wandoko and Panggati, 2022;Arifin and Syah, 2023). Adam et al (2023) argued that e-WOM also can minimize costs of advertising as WOM comes from the personal desire of consumers. Filho and Barcelos (2020) explained that e-WOM can only be formed with consumers positive views or perceptions of the products or services.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to a wider reach, communication through E-WOM is more easily believed that can influence the formation of purchasing decisions (Wandoko and Panggati, 2022;Arifin and Syah, 2023). Adam et al (2023) argued that e-WOM also can minimize costs of advertising as WOM comes from the personal desire of consumers. Filho and Barcelos (2020) explained that e-WOM can only be formed with consumers positive views or perceptions of the products or services.…”
Section: Methodsmentioning
confidence: 99%
“…Then, Anjani et al (2019) found that the marketing mix has a significant influence on loyalty in the traditional market. Adam et al (2023) found that marketing mix has a significant influence on revisit intention.…”
Section: B Visit Intentionmentioning
confidence: 98%
“…Viral marketing is as contagious as a virus, another form of word of mouth, shared by consumers via voice, video, and online writing reviewing products and services developed by companies. Based on previous research from Azhar et al (2022) that the influence of e-WOM has a direct positive influence and significantly on the image of the city, attitudes towards city tourism, and intention to visit, it was revealed that e-WOM also affects the intention to visit indirectly through the image of the city, and also Adam et al (2023) indicates that scholars have recognized various factors with the capacity to impact intentions for revisiting in tourism. These factors encompass eWOM activities, the marketing mix, and the image associated with the destination.…”
Section: Introductionmentioning
confidence: 99%